IMPLEMENTASI KEBIJAKAN ONE VILLAGE ONE PRODUCT (OVOP) TERLAKSANA PADA KAMPUNG RENDANG DI KOTA PAYAKUMBUH - Dasatry Dwi Ramadona; Asep Ajidin (Journal Publicuho, 2024)
The purpose of this research is to understand and analyze the implementation of the One Village, One Product (OVOP) policy in Kampung Rendang, Payakumbuh City, West Sumatra. The thematic analysis method with a qualitative deductive concept was used to identify the driving factors of OVOP policy implementation from the point of view of policymakers and Rendang Small and Medium Industries (SMIs) in the Rendang Village Center. Data collection was conducted through semi-structured interviews. Data processing was done in Nvivo 12 Plus using the saturation technique. The results found that there were 10 factors driving the implementation of OVOP policy from the policymakers and 8 factors driving the implementation of OVOP policy from the SMIs. OVOP policy is the responsibility of the Department of Labor and Industry (Disnakerperin). Disnakerperin has the right to assess the performance of OVOP SMIs and then coordinate it with other responsible parties. Policymakers have provided training, mentoring, promotional platforms, market access, and licensing for Rendang SMIs in the Rendang Village Center. The OVOP policy in Kampung Rendang has generally been successful but still needs to be reviewed for improvement. The research implications emphasize the importance of communication in the substance of a policy. Through communication, it will be easier to mobilize both human resources, information, authority, and the necessary facilities. Bureaucratic structure and disposition also play an important role in determining the success of implementing a policy.